Difficulties Experience of Halal Product Process Assistant During Halal Certification Process - Rizkaprilisa, Windy; Paramastuti, Ratih; Anggraeni, Novia; Nurvita, Silvia; Hapsari, Martina Widhi; Murti, Paulus Damar Bayu (Journal of Digital Marketing and Halal Industry, 2024)
The increase in the issuance of halal certificates will continue to occur every year. Not all business actors understand the halal certification process, so a Proses Produk Halal (PPH) assistant is needed to educate and guide them. PPH assistant experience many obstacles when assisting business actors in registering the halal status of their products. This study aims to analyze the difficulties faced by PPH assistants and formulate ways to overcome these difficulties. Methods of this research use descriptive research that aims to systematically describe or explain a phenomenon that is currently occurring with factual data. The result of this research are most respondents have been PPH assistants for less than 1 year (57%). Business actors apply for halal certification for their products after the products are marketed (47%) and when they are required to be halal certified (53%). The reason business actors apply for halal certification is to follow government regulations (50%). The biggest difficulty experienced by PPH assistants is that business actors need to learn the importance of halal certification for their products (53%). They think that halal certification is a halal product without registering halal (63%). 80% of business actors do not know how to register for halal certification. PPH assistants feel that many business actors do not know how to access the “Si Halal” website (67%). These difficulties result in PPH assistants having different times in the halal certification process, namely more than 3 months (77%), 1-3 months (17%), and less than 1 month (7%).